Obtenção de BIOH 2 a partir da fermentação anaeróbia de efluente de cervejaria utilizando cultura pura isolada do ambiente - Estevam, Andressa (2017)
The search for alternative fuels to replace the current demand for fossil fuels is growing worldwide, as is the case of the use of biomass for the production of clean energy. H2, besides being an important input in the industrial sector, is an excellent fuel due to its calorific value and the non-generation of gaseous pollutants. The production of hydrogen by anaerobic fermentation has been highlighted as an important route of production because it allows the use of residual substrates by microorganisms producing H2. Such microorganisms can be found in many sources in the form of anaerobic microbial consortia, for use in the form of mixed culture or for isolation of species. This work aimed at the isolation of bacteria from the environment, with the capacity to produce hydrogen by anaerobic fermentation of different substrates and the application of these cultures to the production of H2 using as a source of carbon the brewery effluent. Strains of bacteria isolated from avian litter were characterized and tested for potential H2 production in small scale trials, in static bottles and different substrates, in mesophilic condition. From the selection of a strain of better performance, the experiments were carried out in a mechanically stirred reactor, in a batch of 72 hours and using exclusively the brewery effluent. The H2 production occurred in all the tests and the average biogas flow rate was 72 mL h-1, H2 H2 molar flow rate of 1.2 mmol H2 h-1 and H2 content in the biogas of 30 to 40%, being this compound only by CO2 and H2.